Pathophysiological mechanisms and emerging therapeutic strategies for muscle wasting: an integrative review - Huang, Jiahao; Wen, Tianshan; Wei, Huijun; Kang, Jiliang; Lu, Junyue; Zhou, Taian; Wen, Youliang; Huang, Haoyuan (Frontiers in Physiology, 2025)
Muscle wasting is a continuum of diseases that entail incremental skeletal muscle mass, as well as functionality, loss and is an important cause of morbidity, mortality, as well as quality of life reduction. This pathophysiology, diagnosis, as well as emerging treatment of significant muscle wasting illnesses, that is, sarcopenia, cachexia, disuse muscle atrophy, as well as neuromuscular illnesses, entail intricate interactions of defective protein synthetic processes, upregulated proteolysis, inflammatory cytokine activation, defective mitochondria, as well as hormone disturbances. Diagnostic methodologies have progressed from crude body dimension measures to sophisticated imaging modalities, as well as molecular biomarkers, but standardization remains contentious. Treatments entail targeted nutrition, as well as exercise regimes, as well as emerging drugs, as well as regenerative medicine therapies. Preclinical-to-clinical translation gaps, even striking, still exist despite promising advances. Some of these include diagnosis-based inequalities, patients' heterogeneity, limited therapeutic advantages, as well as implementation difficulties within healthcare. Future directions have emphasis on personalized medicine strategies that entail multi-omics signatures, combinatorial therapy of several targets, electronic health platforms for dynamic surveillance, as well as prevention modalities. Integrated healthcare platforms, multinational collaborative platforms, as well as regulatory reforms favoring muscle health across the life continuum, are needed for accomplishing the emerging challenge of controlling emerging muscle wasting burdens of the old, as well as those beset by chronic illnesses.